Pengaruh Celebrity Endorsement oleh NCT Dream pada Produk Tos Tos Terhadap Minat Beli (Purchase Intention) Penggemar NCT Dream di Kalangan Gen Z - Nikita Dewi Anjani Sudrajat; Santi Rimadias (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2025)
The development of globalization has opened up many opportunities in the business world, especially in helping companies increase their sales and profits. One of the increasingly popular marketing tools is the use of celebrity endorsements. In this context, the Korean Wave phenomenon is one of the important aspects that attracts the attention of global consumers, especially in Indonesia. This study aims to encourage the influence of celebrity endorsements from NCT Dream on consumer behavior and purchase intentions for Tos Tos snack products. By involving 161 respondents who are NCT Dream fans who were born between 1997-2012 (Gen Z) and know Tos Tos products. This study uses a quantitative method with data analysis using the PLS-SEM approach supported by SmartPLS 3.0 software. The results of the study showed a significant influence of the Celebrity Endorsement and Consumer Behavior variables on Purchase Intentions for Tos Tos snack products, while the Digital Marketing variable did not have a significant effect on Purchase Intentions. This finding has an impact on Tos Tos to analyze factors that can increase consumer purchase intentions.